Analisis Pengaruh Nilai Tukar Rupiah Per Dolar AS, Tingkat Suku Bunga SBI, Dan Inflasi Indeks Harga Konsumen (IHK) Terhadap IHSG Di BEI Periode 2003-2008 - Fransisca Kurnia; Linda Santioso (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
The financial statement is an important thing for a company. The financial statement of the company can indicate the company's condition and the investors always wait for it to set their investments. The purpose of this survey is to observe whether the Rupiah exchange rate per US Dollars, the Interest rate of SBI and Inflation of Consumer Price Index (CPI) have influenced Composite Stock Price Index at Jakarta Stock Exchange either through partial and also simultaneous. The result shows that the variable of Interest rate of SBI and Inflation of Consumer Price Index (CPI) significantly influence the Composite Stock Price Index. If it is analyzed simultaneously, three variables have significant influences on the Composite Stock Price Index.